Representasi Kekerasan Simbolik Perempuan dalam Film Pasutri Gaje - Lia Fitri Anggarista; Bela Fataya Azmi (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
Violence does not always manifest in physical forms; it can also occur symbolically through subtle forms of domination embedded in language, gestures, and visual representations that normalize gender inequality. The representation of women in media, particularly in film, has the potential to reproduce symbolic violence that remains largely invisible yet becomes normalized in everyday life. Such symbolic violence often operates through meaning-making processes that shape societal perceptions of women’s roles and positions. This study aims to examine the representation of women in relationships characterized by symbolic violence in the film Pasutri Gaje and to identify the meanings constructed through dialogue, gestures, and visual elements within the film. This study employs a descriptive qualitative approach, using scenes and film texts from Pasutri Gaje as the primary data. The analysis is grounded in Stuart Hall’s theory of representation, particularly the constructionist approach, to explore the production of meaning. Data were analyzed using Roland Barthes’ semiotic framework, which consists of three levels of signification: denotation, connotation, and myth, to identify symbols that represent women within the film’s narrative. The findings reveal that women are represented as subordinate figures associated with emotional and domestic myths. These representations reinforce symbolic violence through language, gestures, and visual elements that repeatedly normalize gender inequality within the film’s narrative. The study demonstrates that film, as a cultural text, plays a significant role in reproducing and sustaining patriarchal values and unequal power relations through representations that appear natural and unquestioned.